1992
DOI: 10.1002/ana.410310613
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroimaging strategy in temporal lobe epilepsy: A comparative study of 18FDG‐PET and 99mTc‐HMPAO–SPECT

Abstract: We performed 99mTc-hexamethylpropyleneamineoxime-single-photon emission computed tomography (SPECT) and 18F-fluorodeoxyglucose-positron emission tomography (PET) in 20 epileptic patients with well-lateralized temporal electroencephalographic focus, normal computed tomographic scan, and brain magnetic resonance imaging (MRI) either normal (n = 10) or showing nonspecific changes in the epileptogenic temporal lobe (n = 10). In patients with a normal MRI, PET exhibited focal hypometabolism in 80%, whereas SPECT sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
3

Year Published

1994
1994
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 17 publications
(7 reference statements)
1
24
1
3
Order By: Relevance
“…Interictal studies using '8fluoro-2-deoxy-D-glucose ('*FDG) positron emission tomography (PET) in temporal lobe epilepsy have shown focal hypometabolism in 65-80% of patients (1,32,33). Comparative studies between "FDG PET and 9 9 T~m HMPAO SPECT have shown that where abnormalities of perfusion are demonstrated by SPECT, they correlate with areas of hypometabolism as detected by PET, but that abnormalities are seen less frequently with SPECT than with PET (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Interictal studies using '8fluoro-2-deoxy-D-glucose ('*FDG) positron emission tomography (PET) in temporal lobe epilepsy have shown focal hypometabolism in 65-80% of patients (1,32,33). Comparative studies between "FDG PET and 9 9 T~m HMPAO SPECT have shown that where abnormalities of perfusion are demonstrated by SPECT, they correlate with areas of hypometabolism as detected by PET, but that abnormalities are seen less frequently with SPECT than with PET (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Obwohl die SPECT preiswerter und leichter zugänglich ist als PET, stellt die Anwendung interiktaler SPECTUntersuchungen mit Blutflussmarkern, wie Tc-99m HMPAO und Tc-99m ECD, aufgrund ihrer geringen Sensitivität keine echte Alternative zur PET-Untersuchung mit FDG dar. Eine Minderperfusion in topographischer Korrelation zum elektroenzephalographisch definierten Anfallsursprung wird von den meisten Arbeitsgruppen übereinstimmend bei Temporallappenepilepsien in lediglich in etwa 40-60% der Fälle berichtet [56].…”
Section: Epilepsieunclassified
“…used to lateralize the seizure focus, showing hypometabolism of the temporal lobe with an incidence of 60-90% (7,11,12). However, the hypometabolic zone in PET scans in patients with TLE is usually larger than the underlying lesion and the region that generates the epileptic seizures (13).…”
Section: Summary: Purposementioning
confidence: 99%